At the Intersection of Animal and Area Studies: Fostering Latin Americanist and Caribbeanist Animal Studies - Domínguez, Daisy (Humanimalia, 2016)
This essay discusses how Animal Studies scholarship in Latin American and Caribbean history relates to the wider scholarship in this emerging field. It identifies and explores general themes in recent scholarship and provides pointers for librarians interested in developing collections that will promote this burgeoning field.